NEGOSIASI PEMBEBASAN LAHAN PADA PEMBAGUNAN JEMBATAN BOTON-MUNA DI KELURAHAN PALABUSA - Mujiono Sairun R; Andy Arya Maulana Wijaya; Nastia Nastia; Herman Lawelai (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the Negotiation of Land Acquisition on the Construction of the Boton-Muna Bridge in Palabusa Village. Land is needed for infrastructure development. Therefore, infrastructure development in the form of the Buton-Muna Bridge requires land acquisition to meet increasing development needs, thus requiring land for development. Specially designed for the public interest. Therefore, it is necessary to acquire land for the development of these interests. This study uses descriptive research with a quantitative approach, which is a research method used to examine the condition of natural objects, so the researcher is the key instrument. Research findings indicate that the results of this study indicate that the land acquisition process for the construction of the Buton-Muna Bridge was carried out in accordance with legal requirements. Predicting obstacles requires the efforts of the land acquisition team to overcome these obstacles. In particular, the role of the land acquisition committee is needed to overcome land acquisition constraints. The land acquisition committee is one of the branches of local government that not only plays an important role in land acquisition, but also plays an important role in resolving problems that arise between those who need it and those who own it. is. Obstacles encountered in acquiring land for public purposes.